The Nexus of Local Government Involvement and Marine Sustainable Ecotourism Development: Mediating Role of Supply Chain Management - Totok Wahyu Abadi; A Riyadh Umar Balahmar; Ilmi Usrotin Choiriyah (International Journal of Supply Chain Management, 2020)
Three sub-districts of Minneapolis Sidoarjo regency, which are Sedati, Candi, and Jabon are not only had superior fishery products, but it also has a potential area to be a highly prospective marine ecotourism. This quantitative research aims to analyze the public relations mix of Sidoarjo Regency, empowerment, community participation, supply chain management and sustainable marine ecotourism development. The research data is conducted by distributing questionnaires towards 204 respondents; then, data collection will be coded and analyzed by utilizing multiple linear regression SPSS 20. The findings show that the development of sustainable marine ecotourism affected by several factors; public relations mix, the role of the regional government, empowerment, and community participation, which is 30,1%. The most influential factors are the role of government, empowerment, and community participation. Whereas, the public relations mix that is utilized by the government does not affect the development of sustainable marine ecotourism. The innovation of this research are, first, the role of government that is supported by community participation and empowerment can enhance sustainable marine ecotourism development. Second, the natural, human, budgetary and cultural resources are the primary capital in developing sustainable marine ecotourism.